Modelo de opciones reales y aplicación al mercado petrolero - Adrián Hernández del Valle; Claudia Icela Martínez García (El Trimestre Económico)
We build a Con di tio nal Real Options mo del VORC which allows for cash flows to be probabilistic and contingent on the average behavior of an external va ria ble; and we apply our mo del to the cru de oil mar ket whe re the in flows on an in vest ment pro ject are con tin gent on the sta te of the base —the dif ference bet ween the fu tu res con tract on an un derl ying as set and it’s pri ce for im me dia te de li very at pre sent (or spot pri ce)—. Our main re sult is that the VORC is a better criteria when evaluating projects with conditional, stochastic cashflows.